An analysis of the relationship between pulmonary-aerobic capacity variables defined via pulmonary function tests and anthropometric measurements of different somatotypes (Annals of Medical Research, 2021)
None
Keywords: PFT; Lungs; Somatotype; Anthropometry; Aerobic Capacity.